Penentuan Setting Prioritas Pengembangan Industri Kopi Biji Di Indonesia: Aplikasi Model Goal Programming - Hadi Paramu; Moh. Fathorrozi (Universitas Airlangga, 2011)
This research aims to determine a priority setting in the development of Indonesian coffee bean industry that can sustain the industry using Goal Programming technique. Based on the number policies, 18 goal programming models formulating some priority setting possibilities had been developed. The validation on the value of decision variables in the model showed that there are six valid models. The result suggested that (1) the development policy has to be prioritized to ensure the supply of plantation inputs, (2) the policy of conversion of Robusta areas to Arabica has to consider the economical and biological aspects, (3) the develop-ment policy has to be directed to export and domestic consumption promotion since the industry is considered as an export maximizing and able to satisfy the domestic consumption, and (4) the development policy has to consider the possibility of target conflicts so that a priority setting will not burden the industry economically.